1989
DOI: 10.1016/0140-1971(89)90092-4
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent as forgiver

Abstract: A social cognitive developmental model of forgiveness is described and tested in two studies, the second being a replication of the first. In study 1, 59 subjects in grades 4, 7, 10, college and in adulthood were given a forgiveness interview that assessed six stages of forgiveness development, Rest's DIT measure of justice development, and a religiosity scale. As predicted, there were strong age trends for forgiveness and justice. Both forgiveness and justice were related but distinct constructs. The more one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
5
12

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 13 publications
9
187
5
12
Order By: Relevance
“…Tsang et al suggested that religion might be used to either encourage forgiveness or justify holding grudges, depending on the nature of one's religion [16]. Several study found that religious individuals are more likely to value forgiveness than those who are not religious [17]- [20], [31]- [32]. Our findings also support this argument in Aceh conflict fictims sample.…”
Section: Discussionsupporting
confidence: 81%
“…Tsang et al suggested that religion might be used to either encourage forgiveness or justify holding grudges, depending on the nature of one's religion [16]. Several study found that religious individuals are more likely to value forgiveness than those who are not religious [17]- [20], [31]- [32]. Our findings also support this argument in Aceh conflict fictims sample.…”
Section: Discussionsupporting
confidence: 81%
“…Accordingly, the present research does not provide any information about the consistency or stability of the lay representation of forgiveness across the life-span. Previous research (Enright, Santos, & Al-Mabuk, 1989) has documented unique differences across ages in how participants' reason about granting forgiveness, similar to Kohlberg's (1969) findings on moral reasoning. These findings have been replicated in a non-western sample (Park & Enright, 1997); however, all of this research was again based on participants' procedural knowledge of granting forgiveness and did not specifically examine if participants at different ages had unique conceptualizations or definitions of forgiveness.…”
Section: Limitationssupporting
confidence: 57%
“…; A1-Mabuk, Enright, & Cardis, 1995;Coyle & Enright, 1997;Enright, Gassin, & Wu, 1992;Enright & Human Development Study Group, 1996;Enright et al, 1989;Freedman & Enright, 1996;Hebl & Enright, 1993; see also MeCullough & Worthington, 1995), scientific progress in the socialpsychological study of interpersonal forgiving has been slow (Baumeister, Exline, & Sommer, 1998;McCullough, Exline, & Baumeister, 1998;McCullough, Rachal, Sandage, & Worthington, 1997;McCullough & Worthington, I994a, 1994b). We believe that along with the slow development of theory, the slow development of psychometric instruments to measure forgiving has also been a major barrier to scientific progress in social and personality psychology .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, preliminary research suggests that the disposition to forgive others loads on the Agreeableness factor of the Big Five (Manger, Saxon, Hamill, & Pannell, 1996). Other such variables might include the sophistication of one's reasoning about forgiveness (e.g., Enright, Santos, & AI-Mabuk, 1989), dissipation-rumination (Caprara, 1986;Caprara, BarbaraneUi, & Comrey, 1992), attitudes toward revenge (Emmons, 1992;Stuckless & Goranson, 1992), and general styles of responding to anger (e.g., Tangney, Wagner, Hill-Barlow, Marschall, & Gramzow, 1996). These personality processes might influence forgiving by facilitating certain relational styles (Asendorpf & Wilpers, 1998) or by disposing people to experience some cognitions (e.g., attributions) or affects (e.g., empathy) regarding an interpersonal offense or offender (while restraining them from experiencing others).…”
Section: Personality-level Determinants Of Forgivingmentioning
confidence: 99%